Awareness study of passive ventilation system in office building - Chua, Kheng Ee; Chan, Siew Chong (INTI International University, 2018)
Heavy dependence onto artificial air-conditioning systems to control the temperature of indoor environment of office buildings has been creating serious global environmental issues due to its nature of high energy consumption. Many research works show that passive ventilation systems may be one of the effective strategies to overcome this key problem through of the approaches to integrate the passive ventilation designs with the building design, such as building orientation, proper shading, thermal insulation, air well design, window selection and others. This research is thus focused onto identifying the awareness of passive ventilation system application in office buildings, and this further leads to compare the extent of awareness of this approach based on two different groups of office users. The research tool used in this study is Descriptive Statistics which consists of Mean-Standard Deviation Analysis and Priority Ranking based on Average Index. The results show that both groups of users have low awareness level of Passive Ventilation System application in office buildings, however Group A show high level of acceptability than Group B. Thus, it is important for the future policy makers to intensify the implementation of Passive Ventilation approach to increase the awareness level of the users in the near future.